2019
DOI: 10.1073/pnas.1821109116
|View full text |Cite
|
Sign up to set email alerts
|

Music training, music aptitude, and speech perception

Abstract: GM (2018) Inherent auditory skills rather than formal music training shape the neural encoding of speech.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 10 publications
0
19
1
Order By: Relevance
“…While the aforementioned studies suggest that musical training can improve speech-in-noise perception, they are cross-sectional studies which should preclude causal inferences (Schellenberg, 2019); further, not all studies have found an effect (Ruggles et al, 2014; Boebinger et al, 2015; Madsen et al, 2017, 2019). One way to resolve these inconsistencies is through the evaluation of musical training outcomes in a controlled experimental design (i.e., a longitudinal context), which a handful of studies have sought to do.…”
Section: Introductionmentioning
confidence: 99%
“…While the aforementioned studies suggest that musical training can improve speech-in-noise perception, they are cross-sectional studies which should preclude causal inferences (Schellenberg, 2019); further, not all studies have found an effect (Ruggles et al, 2014; Boebinger et al, 2015; Madsen et al, 2017, 2019). One way to resolve these inconsistencies is through the evaluation of musical training outcomes in a controlled experimental design (i.e., a longitudinal context), which a handful of studies have sought to do.…”
Section: Introductionmentioning
confidence: 99%
“…Considered cumulatively, an emerging theoretical framework suggests that associations between musicality and language skills could be driven by genetic correlations (Ladanyi et al, 2020;Schellenberg, 2019). First, family-based approaches (primarily twin studies) have shown moderate heritability of musicality across objective and subjective measures, including music perception, achievement, interest, and practice habits in adolescents and adults (Coon & Carey, 1989;Hambrick & Tucker-Drob, 2015;Mosing et al, 2014a;Ullén et al, 2014;Vinkhuyzen, van der Sluis, Posthuma, & Boomsma, 2009).…”
Section: Music Engagment and Verbal Abilitymentioning
confidence: 99%
“…Second, there is only limited meta-analytic evidence that music lessons enhance language skills in children and young adults (Gordon, Fehd, & McCandliss, 2015a;Sala & Gobet, 2017). Indeed, a substantial body of work that initially interpreted superior performance on speech/language tasks as a transfer from musical training to language expertise (e.g., Patel, 2014) is now being revisited as evidence of self-selection for music training (Bidelman & Mankel, 2019;Schellenberg, 2019). These patterns of findings are highly consistent with genetic correlations, wherein individuals with genetic predispositions for stronger language or cognitive abilities are more likely to seek out musical training (i.e., self-selection or pleiotropy).…”
Section: Music Engagment and Verbal Abilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The improved cortical activities in musicians exhibit experience-driven neural changes (Shahin et al, 2003 ; Marques et al, 2007 ; Seppänen et al, 2012 ). However, some studies have suggested that the neuroplasticity evidence in musicians may be an innate property in people whose auditory function is superior to others rather than music experience-driven factors (Schellenberg, 2015 , 2019 ; Mankel and Bidelman, 2018 ).…”
Section: Introductionmentioning
confidence: 99%